2013
DOI: 10.1039/c3nr30071d
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles induce transcriptional activity of NF-κB in a B-lymphocyte cell line

Abstract: Gold nanoparticles (Au-NPs) have been designated as superior tools for biological applications owing to their characteristic surface plasmon absorption/scattering and amperometric (electron transfer) properties, in conjunction with low or no immediate toxicity towards biological systems. Many studies have shown the ease of designing application-based tools using Au-NPs but the interaction of this nanosized material with biomolecules in a physiological environment is an area requiring deeper investigation. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…Dokić et al (2012), who analyzed the influence of different fractions of AuNPs obtained by ultrasonic spray pyrolysis from gold scrap on ConA stimulated rats' splenocytes, observed that smaller and less agglomerated particles increased the synthesis of IL-2 while inhibiting the synthesis of IL-10, which resembles the effect obtained in our experiment at the medium dose of AuNPs. What is more, in studies on mouse B lymphocytes, AuNPs passed through the cytoplasmic membrane of cells, activating the cells and elevating the expression of antibodies (Sharma et al 2013). A similar outcome was observed in vivo by Dykman et al (2004), who analyzed the influence of AuNPs on the immunological response of laboratory animals (rabbits, rats and mice).…”
Section: Discussionmentioning
confidence: 59%
“…Dokić et al (2012), who analyzed the influence of different fractions of AuNPs obtained by ultrasonic spray pyrolysis from gold scrap on ConA stimulated rats' splenocytes, observed that smaller and less agglomerated particles increased the synthesis of IL-2 while inhibiting the synthesis of IL-10, which resembles the effect obtained in our experiment at the medium dose of AuNPs. What is more, in studies on mouse B lymphocytes, AuNPs passed through the cytoplasmic membrane of cells, activating the cells and elevating the expression of antibodies (Sharma et al 2013). A similar outcome was observed in vivo by Dykman et al (2004), who analyzed the influence of AuNPs on the immunological response of laboratory animals (rabbits, rats and mice).…”
Section: Discussionmentioning
confidence: 59%
“…The rise observed in the percentage of B cells can easily be explained by their stimulation by nanoparticles, which has been confirmed by other research. In a line of murine B lymphocytes (CH12.LX), AuNPs passed through the cytoplasmic membrane, thus activating the cells and stimulating antibody production (Sharma et al 2013). A similar effect was achieved in vivo by Dykman et al (2004) in rabbits, rats and mice immunized with haptens or complete antigens.…”
Section: Discussionmentioning
confidence: 64%
“…58,[91][92][93] These interactions include (1) genotoxic e®ects caused by high levels of ROS and (2) proteins/ enzymes dysregulation induced by Au NP exposure. For example, Sharma and coauthors have investigated the interactions of citrate-capped Au NPs (D core ¼ 10 nm) with murine B-lymphocyte cells (CH12.LX).…”
Section: Intracellular Signaling Pathways and Genotoxicitymentioning
confidence: 99%